THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES REGARDING THE USE OF PPE IN THE COVID-19 PANDEMIC PERIOD OF NERS PROFESSIONAL STUDENTS IN SLEMAN DISTRICT - Jennifa; Dwi Agustiana Sari; Livia Nurlatu (PROFESSIONAL HEALTH JOURNAL, 2022)
COVID-19 was officially declared a global pandemic case by WHO. Based on WHO data in May 2020, there were 989 health workers who died from COVID-19 worldwide. The increase in positive cases for health workers is caused by comorbid or congenital diseases and also inadequate PPE. PPE is very important for the protection of the health workers themselves and the patients they treat. Research purpose to find out the relationship between knowledge and attitudes about the use of PPE during the COVID-19 pandemic among Nursing Professional students in Sleman Regency. This research is a type of descriptive correlation research, and uses a quantitative method with a cross sectional approach. The number of samples in this study were 109 people with the sampling method used was purposive sampling. The instrument used in this study was a knowledge and attitude questionnaire about the use of PPE, with the analysis used, namely univariate and bivariate. Research result there is a relationship between knowledge and attitudes about the use of PPE during the COVID-19 pandemic among Nursing Professional students in Sleman Regency. The majority of the level of knowledge possessed by Nursing Profession students in Sleman Regency is high and the majority of attitudes possessed by Nursing Profession students in Sleman Regency are good. There is a relationship between the level of knowledge and attitudes about using PPE during the COVID-19 pandemic. It is hoped that this will increase knowledge and understanding of the use of PPE during the COVID-19 pandemic for Nursing Profession students in Sleman Regency. Keywords: Attitudes, COVID-19, Knowledge